(untitled) (Archive of Conferences, 2022)
Winged words have a great role in the national and the world culture. They are the words of great philosophers, scientists, writers and statesmen. They are the word combinations, which make our speech more meaning ful. The following article discusses the winged words that serve to express the treacherous nature observed in some individuals.